Strategi Inovatif dalam Pelayanan Publik: Mengintegrasikan Teknologi untuk Responsivitas yang Lebih Baik - Putri, Desi Riani Dwi; Tjenreng, Muhammad Baharuddin Zubakhrum (Jurnal PKM Manajemen Bisnis, 2025)
In the context of public services in the digital era, innovative strategies have become key to enhancing responsiveness and the quality of services provided to the public. In Indonesia, various initiatives have been undertaken to integrate technology into public services. The Central Statistics Agency (BPS) recorded that in 2019, the Integrated Statistical Services achieved a public service index score of 4.39, placing it third among 54 ministries and agencies that were evaluated. Despite these advancements, challenges remain. Common issues in public services include unclear procedures, uncertainty regarding service times, and the competence of staff. The research method used in this study is qualitative, specifically a literature review. The findings suggest that innovative strategies in public services through the integration of technology not only have the potential to enhance responsiveness but also to build trust between the government and the public. By adopting an inclusive approach that is focused on the needs of the public, public services can be transformed to become more efficient, transparent, and responsive to social dynamics. The success of this strategy depends on collaboration among various stakeholders and a commitment to continuously adapting to rapid technological developments.